Tolerance induction after specific immunotherapy with pollen allergoids adjuvanted by monophosphoryl lipid A in children - Rosewich, M (Blackwell Science Inc, 2010)
Specific immunotherapy (SIT) is a well-established and clinically effective treatment for allergic diseases. A pollen allergoid formulated with the T helper type 1 (Th1)-inducing adjuvant monophosphoryl lipid A (MPL) facilitates short-term SIT. Little is known about mechanisms of tolerance induction in this setting. In a prospective study, 34 patients allergic to grass pollen (25 male, nine female, median age 10·2 years) received a total of 44 SIT courses (20 in the first, 24 in the second) with MPL-adjuvanted pollen allergoids. Immunogenicity was measured by levels of specific immunoglobulin G (IgG(grass)) and IgG4(grass) by antibody blocking properties on basophil activation, and by induction of CD4(+), CD25(+) and forkhead box P3 (FoxP3(+)) regulatory T cells (T(reg)). Specific IgG and IgG4 levels increased only slightly in the first year of SIT. In the second year these changes reached significance (P < 0·0001). In keeping with these findings, we were able to show an increase of T(reg) cells and a decreased release of leukotrienes after the second year of treatment. In the first year of treatment we found little evidence for immunological changes. A significant antibody induction was seen only after the second course of SIT. Short-course immunotherapy with pollen allergoids formulated with the Th1-inducing adjuvant MPL needs at least two courses to establish tolerance.